Population change and economic development in East Asia challenges met, opportunities seized - Mason, Andrew 1947- (Contemporary issues in Asia and the Pacific, 2001)
"This volume is the result of a project initiated by the East-West Center. Papers were presented at three meetings held in 1997: the Conference on Population and the Asian Economic Miracle, East-West Center, Honolulu, HI, January 7-10, 1997; a Learning Forum on Demographic Momentum and Macroeconomics, the World Bank Institute and the East-West Center, Washington, DC, July 21-22, 1997; and the Policy Seminar on Asian Economic Development: Long Term Perspectives, Nihon University, East-West Center, and the World Bank Institute, Tokyo, October 20-21, 1997" --Preface.